cot a/1+tan a = cot a-1/2-sec^2 a
Answers
Answered by
1
cotA - 1 / 2 - sec^2A = cotA / 1 + tanA
LHS
= cotA - 1 / 2 - sec^2A
= (cosA/sinA - 1) / 1 + 1 - sec^2A
= [(cosA - sinA) / sinA] / 1 - tan^2A
= [(cosA - sinA) / sinA] / [1 - sin^2A / cos^2A]
= [(cosA - sinA) / sinA] / [(cos^2A - sin^2A) / cos^2A]
= (cosA - sinA) / sinA X cos^2A / (cosA + sinA) (cosA - sinA)
= cos^2A / sinA (cosA + sinA)
RHS
= cotA / 1 - tanA
= (cosA / sinA) / (1 - sinA/cosA)
= (cosA / sinA) / [(cosA - sinA) / cosA]
= cosA / sinA X cosA / (cosA - sinA)
= cos^2A / sinA (cosA + sinA)
LHS = RHS
Hence proved.
Thanks me
Mark me as brainliest :-)
Answered by
1
Answer:
here is your answer
Step-by-step explanation:
Do mark it brainly
Attachments:
![](https://hi-static.z-dn.net/files/d25/1e82b3fb76a985b245045c2b684c0db3.jpg)
Similar questions
Math,
5 months ago
Science,
5 months ago
English,
10 months ago
History,
10 months ago
Social Sciences,
1 year ago